Should transmission electron microscopy and ultrastructural cilia evaluation remain part of the diagnostic work-up for primary ciliary dyskinesia? - Werner, Claudius; Kouis, Panayiotis (My University, 2017)
The diagnostic work-up for primary ciliary dyskinesia (PCD) traditionally includes ciliary ultrastructural assessment using transmission electron microscopy (TEM). However, the identification of genetic variants of PCD that are missed by TEM, along with the development of novel diagnostic modalities for PCD that allow structural evaluation of cilia, such as immunofluorescence analysis and the increased availability of genetic testing, calls into questioning the contemporary role of TEM in the diagnostic work-up for PCD. In this manuscript, we describe the evidence for and against the use of TEM in PCD diagnosis, in light of recent developments of PCD.
Keywords: Cilia; PCD diagnosis; Transmission electron microscopy